STEM Education through the Perspectives of Secondary Schools Teachers and School Administrators in Turkey - ÇEVİK, Mustafa and ÖZGÜNAY, Esma (Asian Journal of Education and Training, 2018)
The aim of this study is to explore the views of science, mathematics and information technologies teachers working in secondary schools and administrators of the schools, in which these teachers are working, regarding STEM. This research is based on a survey model in which quantitative data tools were used to directly obtain the opinions of teachers about STEM education; in parallel qualitative data tools were used to deeply understand the views of administrators about STEM education. The sample of the study consisted of 136 STEM field educators working in 21state and private public secondary schools and 45 administrators working in these schools. While views of teachers indicated that the impact of STEM on students was higher than its effect on courses and teachers with each subscale of the quantitative data collection tool conducted with teachers, no significant relation was observed between these findings, gender and branch variables. Similarly, administrators stated that STEM is more effective on the students, teachers are not well equipped to teach STEM, they need to train themselves to implement STEM in courses and curriculums should be prepared on a STEM basis.